Peningkatan Pengetahuan dan Deteksi Dini Hiperurisemia melalui Edukasi dan Pemeriksaan Asam Urat pada Lansia di Masyarakat - Muhammad Basri; Nasrullah Nasrullah (Jurnal Inovasi Pengabdian Masyarakat Celebes, 2026)
Hyperuricemia is a metabolic disorder that often occurs in the elderly and can progress to gout and other metabolic complications. Many elderly people are unaware of their elevated uric acid levels because symptoms often appear at an advanced stage. Health education and uric acid level testing are important strategies to increase knowledge and support early detection in the community. This study aims to analyze the increase in knowledge and support early detection of hyperuricemia through educational activities and uric acid level testing in the elderly. The study used a cross-sectional design in a community service activity conducted in Bungi Community Health Center in December 2025. A sample of 35 elderly people was selected using a purposive sampling technique. Data were collected through a knowledge questionnaire and uric acid level testing. Data were analyzed using univariate, bivariate, and multivariate methods using logistic regression. Health education significantly improved the elderly's knowledge level. Consumption of high-purine foods, body mass index, and a history of hyperuricemia were associated with elevated uric acid levels. Health education and uric acid examinations are effective in increasing knowledge and supporting early detection of hyperuricemia in the elderly in the community.